Phosphodiesterase 4 (PDE4) regulation of proinflammatory cytokine and chemokine release from rheumatoid synovial membrane. Issue 6 (21st February 2011) - Crilly, Anne; Robertson, Susan E; Reilly, James H; Gracie, J Alastair; Lai, Wen-Qi; Leung, Bernard P; Life, Paul F; McInnes, Iain B
Abstract : Background: The cAMP-metabolising enzyme, phosphodiesterase 4 (PDE4), has been implicated in a number of immune responses, including tumour necrosis factor α (TNFα) production. To date, few data have directly addressed whether synovial cytokine and chemokine production is modified by PDE4. Objective: Using specific PDE4 inhibitors, roflumilast plus two novel inhibitors, INH 0061 and INH 0062, the authors studied the effect of PDE4 inhibition on proinflammatory cytokine and chemokine release from primary rheumatoid arthritis (RA) synovial digest suspensions and in a macrophage T cell co-culture assay system. Results: All PDE4 inhibitors dose-dependently reduced the release of TNFα from primary synovial membrane cultures (n=5), half maximal inhibitory concentration (IC50 ) 300–30 nM, p<0.05. Similarly, a significant suppression in the release the proinflammatory chemokines, monocyte chemoattractant protein-1 (MCP-1), macrophage inflammatory protein (MIP)-1α, MIP-1β (IC50 300–30 nM) and regulated upon activation normal T-cell expressed and secreted (RANTES) (IC50 3 nM) was also observed, p<0.05. While interleukin 1β was also reduced, it did not achieve an IC50 . These observations were further confirmed in a macrophage T cell co-culture system, demonstrating the importance of PDE4 pathways in regulating cytokine/chemokine release in a cellular interaction implicated in inflammatory synovitis. Subsequent studies using the human monocytic cell line U937 also demonstrated cytokine regulation with PDE4 knockdown utilising a small interfering RNA approach. Conclusion: These data provide direct evidence of PDE4-dependent pathways in human RA synovial inflammatory cytokine and chemokine release and may provide a novel approach in treating chronic autoimmune conditions such as RA.